The economics of international adjustment - Hinshaw, Randall Weston (Baltimore : Johns Hopkins Press, 1971)
This book is a conference proceedings. It contains dialogues from the Claremont Conference in 1944, which voiced the concern from several economists of the time on how countries can deal with their external payments problems without jeopardizing their other economic objectives.
Includes bibliographical footnotes and index
usc 08/05/2018; 07/08/2018; 07/11/2018
Loans
Keywords: Foreign exchange rates; Balance of payments